Seasonal changes in jump performance in elite female volleyball athletes - Gonzalez-Rave, J. M.; Martinez Valencia, M. A.; Clemente Suarez, V.; Juarez, D.; Navarro Valdivielso, F. (Archivos de medicina del deporte, 2008)
Volleyball is an intermittent sport that requires players to compete in frequent short bouts of high-intensity exercise, followed by periods of low intensity activity. The effect of reducing strength and power training programmes has been reported for competition periods up to 16 weeks which is considerably shorter than the 32 week volleyball league season in Spain. An investigation is required to examine the effect of training program over the course of a long competition period. The purpose of this study was to document seasonal changes in jump performance (Squat Jump, Countermovement Jump and Abalakov) of women volleyball players at Bargas Atalia Team. The independent variable was a annual cycle designed like block periodization. The block concept suggests consecutive training stimulation of carefully selected fi tness components. The rational sequencing of specialized mesocycle-blocks presupposes the exploitation and superimposition of residual training effects. 11 women volleyball players from Bargas Atalia Team participated in this study. Jump performance was measured at 4 time points over a 1 year period in Spanish female Volleyball Super league. In order to determinate whether there were seasonal changes in these test, subjects were tested in august, immediately following 4 weeks of strength and conditioning (September), following 4 weeks of prior to the regular competitive season (October), and following 16 week of regular competitive season (February). In SJ Mean jump height showed signifi cant differences between august and February (p<0,01) and September and February (p<0.05). the results for CMJ showed signifi cant differences between august and February (p<0,01). Jump height in Abalakov showed significant differences between august and February (p<0,00) and September and February (p<0.01). It was concluded that eight weeks of pre-season may have a limited role in determining the success of the power in- season and after 16 weeks of regular season and training program the power increased signifi cantly